2008
DOI: 10.1080/09603100701704272
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rational and irrational sentiments of individual and institutional investors on DJIA and S&P500 index returns

Abstract: We examine the relative effects of rational and irrational investor sentiments on Dow Jones Industrial Average and S&P500 returns. The impact of rational sentiments on stock market returns is found to be greater than that of irrational sentiments. There are immediate positive responses of stock market returns to irrational sentiments corrected by negative responses in the upcoming periods. There are positive effects of past stock market returns on irrational sentiments but not on rational sentiments. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 54 publications
9
59
2
Order By: Relevance
“…What is also surprising is that sentiment is exogenous at least up to lag four while in many related studies in the literature strong causation from returns on sentiment is found. Note also that our trading experiments show that the sentiment data can not be interpreted as an inow of information on Sunday evening whose release is incorporated into prices as soon as trading starts 13 See Mizon (1995) for the general methodology and Hoover and Perez (1999) for Monte Carlo evidence on successful specication search under this approach. again on Monday morning.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…What is also surprising is that sentiment is exogenous at least up to lag four while in many related studies in the literature strong causation from returns on sentiment is found. Note also that our trading experiments show that the sentiment data can not be interpreted as an inow of information on Sunday evening whose release is incorporated into prices as soon as trading starts 13 See Mizon (1995) for the general methodology and Hoover and Perez (1999) for Monte Carlo evidence on successful specication search under this approach. again on Monday morning.…”
Section: Resultsmentioning
confidence: 97%
“…While we recover predictability and protability only for constrained VAR models estimated via least squares, this is the theoretically preferred structure of our VAR estimation given the many insignicant parameters and the results of specication tests. Our most successful specication -the restricted VAR(5) estimated via least squares-could be seen as the adaptation of a straightforward general-to-specic approach to our setting 13 . However, although the success of our VAR models in the forecasting and trading exercises depends crucially on an appropriate specication, the results on causality are extremely robust.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they only investigate the effect of investor sentiment on stock returns. The effect of foreign investor sentiments in emerging stock market returns and volatility is not fully examined (Verma, Baklaci, & Soydemir, 2008;Verma & Soydemir, 2006). Therefore, this study examines the impact of the U.S. institutional investor sentiment on the ISE returns and volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When selecting sentiment proxies, there are mainly two ways. Foreign scholars usually uses direct way to express personal and institutional investor sentiment [7]. By contrast, domestic scholars both use direct and indirect ways [8,9].…”
mentioning
confidence: 99%